Quantum Estimates of Alpha Emitter Life Time - B. Santoso (Atom Indonesia, 2006)
Quantum estimates of several alpha radioactive life time have been made using the probability of quantum tunneling through the nuclear potential barrier. It is assumed that for a given nucleus with mass number A and isotopic number Z, there exists an alpha particle moving freely back and forth in the nucleus with mass and isotopic numbers A -4 and Z-2. If the probability of penetrating the nuclear potential barrier is Τ, then after N times (N=1/Τ) hitting the barrier an alpha particle is emitted. To obtain the elapsed time for emitting an alpha particle requires N times τ0, where τ0 is the time travel for alpha across the nuclear diameter, which is dependent on alpha energy. It is assumed here that this kinetic energy is the same as the emitted energy. The emitting alpha kinetic energies here are calculated by the difference of the masses of the parent and daughter nuclei and the alpha particles. They are in closed agreement with the experimental observations. While the alpha radioactive life time are not the same order of magnitudes but give the same linearity on the logarithmic scale as function of the inverse square root of energy.